2001
DOI: 10.1034/j.1600-0714.2001.300908.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary albumin, total protein, IgA, IgG and IgM concentrations and occurrence of some periodontopathogens in HIV‐infected patients: a 2‐year follow‐up study

Abstract: HIV infection reduces oral defensive mechanisms and may affect mucosal integrity. Differences in salivary protein concentrations and periodontopathogenic bacteria were studied in 56 HIV-infected patients with respect to their disease phase. Thirty-three patients were followed up for 2 years. Fifty-three healthy subjects of corresponding age and sex were studied as controls. At baseline, salivary albumin, total protein, IgA, and IgM levels were significantly higher (P<0.05-0.0001) in all phases of HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Previous studies have consistently shown that P. gingivalis was significantly more prevalent in both supra-and subgingival plaque samples from periodontitis subjects compared to those from healthy individuals (10,31). Results from independent studies indicate that periodontopathogens, including P. gingivalis, were detected more frequently and were found at higher levels in HIV-infected patients than in noninfected control subjects with similar periodontal statuses (5,20,26,33). On the contrary, recent results from Patel et al (23) showed a significant prevalence of Porphyromonas gingivalis and Treponema denticola among HIV-negative patients compared to that among HIV-positive patients.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have consistently shown that P. gingivalis was significantly more prevalent in both supra-and subgingival plaque samples from periodontitis subjects compared to those from healthy individuals (10,31). Results from independent studies indicate that periodontopathogens, including P. gingivalis, were detected more frequently and were found at higher levels in HIV-infected patients than in noninfected control subjects with similar periodontal statuses (5,20,26,33). On the contrary, recent results from Patel et al (23) showed a significant prevalence of Porphyromonas gingivalis and Treponema denticola among HIV-negative patients compared to that among HIV-positive patients.…”
Section: Discussionsupporting
confidence: 52%
“…All analyses were made in duplicates with serum standards and appropriate controls. For details, see Mellanen et al [25].…”
Section: Saliva Sampling and Analysesmentioning
confidence: 98%
“…Because albumin is ubiquitous in the body and is one of the most abundant proteins in secretions of the upper respiratory tract (Mellanen et al, 2001), saliva is a logical candidate for biomonitoring (Jeppsson et al, 2009; Kristiansson et al, 2004). Our results, summarized in Figure 4, indicate that comparable background concentrations of formyl adducts were detected in saliva and blood from the volunteer subject whose biospecimens were used for in vitro experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, immunoassays have detected putative antibodies against formaldehyde-HSA (human serum albumin) conjugates in the blood of exposed workers and smokers (Carraro et al, 1999; Ospina et al, 2011; Pala et al, 2008). Albumin is also abundant in respiratory fluids and saliva where reactions with inhaled formaldehyde would be expected (Aldini et al, 2008; Chung et al, 2013; Mellanen et al, 2001; Meurman et al, 2002; Mochca-Morales, 2000) with subsequent transfer to the blood.…”
Section: Introductionmentioning
confidence: 99%